Antiphospholipid Autoantibodies in Women with Recurrent Gestational Failures – Controversies in Management - Segovia, Aurea Garcia; Rodriguez-Mahou, Margarita; Caballero, Pedro; Sanchez-Ramon, Silvia (IntechOpen, 2012)
None